“Juan Bautista Alberdi: thinker of the Argentine education”: Roca’s creation to defend the program of the possible republic at the end of the 19th century (Quinto Sol, 2014)
If we focus on the educational field, which is the one we are more interestedin, we can see that Roca, during his second presidency, tries to make a drastic change in the public educational system in order to eliminate the exclusively political function of the education and create another system following Alberdian postulates.
Keywords: Roca; Alberdi; education; Argentine